A Cohort Study of the Milk Microbiota of Healthy and Inflamed Bovine Mammary Glands From Dryoff Through 150 Days in Milk - Metzger, Stephanie A.; Hernandez, Laura L.; Skarlupka, Joseph H.; Walker, Teresa M.; Suen, Garret; Ruegg, Pamela L. (Frontiers in Veterinary Science, 2018)
The objective of this longitudinal cohort study was to describe the milk microbiota of dairy cow mammary glands based on inflammation status before and after the dry period. Individual mammary quarters were assigned to cohorts based on culture results and somatic cell count (SCC) at dryoff and twice in the first 2 weeks post-calving. Mammary glands that were microbiologically negative and had low SCC ( < 100,000 cells/mL) at all 3 sampling periods were classified as Healthy. Microbiologically negative mammary glands that had SCC ≥ 150,000 cells/mL at dryoff and the first post-calving sample were classified as Chronic (CHRON; n = 17). Quarters that did not have both culture-negative milk and SCC ≥ 150,000 cells/mL at dryoff but were culture-negative with SCC > 150,000 at both post-calving sampling periods were classified as New Inflammation (NEWINF; n = 6). Mammary glands with bacterial growth and SCC >150,000 cells/mL at all 3 periods were classified as Positive (POS; n = 3). Milk samples were collected from all enrolled quarters until 150 days in milk and subjected to microbiota analysis. Milk samples underwent total DNA extraction, a 40-cycle PCR to amplify the V4 region of the bacterial 16S rRNA gene, and next-generation sequencing. Healthy quarters had the lowest rate of PCR and sequencing success (53%, 67%, 83%, and 67% for Healthy, CHRON, NEWINF, and POS, respectively). Chao richness was greatest in milk collected from Healthy quarters and Shannon diversity was greater in milk from Healthy and CHRON quarters than in milk collected from glands in the NEWINF or POS cohorts. Regardless of cohort, season was associated with both richness and diversity, but stage of lactation was not. The most prevalent OTUs included gut- and skin-associated bacteria such as those in the phylum Bacteroidetes and the genera Enyhdrobacter and Corynebacterium. The increased sequencing success in quarters with worse health outcomes, combined with the lack of bacterial growth in most samples and high PCR cycle number required for amplification of bacterial DNA, suggests the milk microbiota of culture-negative, healthy mammary glands is less abundant than that of culture-negative glands with a history of inflammation.